Kajian Dendrimer (Poly)Amidoamine (Pamam) Generasi 4 Sebagai Template Dalam Pembentukan Nanopartikel Secara In Silico - Yurika Sastyarina; Zuhrotun Nafisah; Muhammad Yusuf; Martalena Ramli; Abdul Mutalib; Ukun Soedjanaatmadja (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2017)
Dendrimers are a class of highly branched synthetic polymers that has spherical form consist of three components: core, branch and terminal functional groups. One of dendrimer that has been commercialized is (Poly)amidoamine (PAMAM). PAMAM dendrimer used as a template in the preparation of gold nanoparticles. This research was studied the streched cavities of (Poly)amidoamine (PAMAM) dendrimer generation 4 using in silico method. Structure of (Poly) amidoamine (PAMAM) dendrimers generation 4 downloaded from Building Toolkit (DBT) Library and before the simulation structure was prepared. Then molecular dynamics simulations run using the AMBER program at 37°C in aqueous conditions. From analysis, obtained that the furthest distance of streched cavities at the closest distance from the core, region between residues 2 and 3 is 23.696 Å and at the terminal region between residues 100 and 122 is 58.045 Å